VD_FINDINFO HC / 2016 / 308 vom 21. März 2016 - VD Tribunal cantonal (2016)
FORMALISME EXCESSIF, VICE DE FORME, RETRAITVOIE DE DROIT, EXPULSION DE LOCATAIRE, CHOSE JUGÉE | 63 al. 1 CPC (CH), 65 CPC (CH)